Global trends of monkeypox-related articles: A bibliometric analysis over the last five decades (1964 - July 14, 2022) - Manar A. Kamal; Ramadan A. Farahat; Ahmed K. Awad; Shehroze Tabassum; Fatma Labieb; Cosmin A. Bejan; Jaffar A. Al-Tawfiq; Kuldeep Dhama; Ismail Dergaa (Elsevier, 2023)
Background: The first human monkeypox (MPX) case was identified in the Democratic Republic of Congo (DRC) in 1970 with an outbreak in 2010 and the first human MPX case in the UK in 2022. In this study, we conducted a bibliometric analysis of the literature on monkeypox based on the Web of Science Core Collection (WOSCC) of the Institute for Scientific Information (ISI) to identify relevant topics and trends in monkeypox research. Methods: We searched the Web of Science from 1964 until July 14, 2022, for all publications using the keywords "Monkeypox" and "Monkeypox virus." Results were compared using numerous bibliometric methodologies and stratified by journal, author, year, institution, and country-specific metrics. Results: Out of 1170 publications initially selected, 1163 entered our analysis, with 65.26 % (n = 759) being original research articles and 9.37 % (n = 109) being review articles. Most MPX publications were in 2010, with 6.02 % (n = 70), followed by 2009 and 2022 at 5.67 % (n = 66) each. The USA was the country with the highest number of publications, with n = 662 (56.92 %) of total publications, followed by Germany with n = 82 (7.05 %), the UK with n = 74 (6.36 %), and Congo with n = 65 (5.59 %). Journal of Virology published the highest number of MPX publications, followed by Virology Journal and Emerging Infectious Diseases with n = 52 (9.25 %), n = 43 (7.65 %), and n = 32 (5.69 %) publications, respectively. The top contributing institutions were the Centers for Disease Control and Prevention (CDC), the US Army Medical Research Institute of Infectious Diseases, and the National Institutes of Health (NIH)National Institute of Allergy and Infectious Diseases (NIAID). Conclusion: Our analysis provides an objective and robust overview of the current literature on MPX and its global trends; this information could serve as a reference guide for those aiming to conduct further MPX-related research and as a source for those seeking information about MPX.